2011
DOI: 10.1007/s00540-011-1185-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors associated with mortality in patients undergoing emergency surgery for abdominal aortic aneurysms

Abstract: The authors clarified that certain features such as age, persistent preoperative shock, and greater amounts of transfusion associated with greater blood loss and anemia were factors affecting the mortality in patients undergoing emergency surgery for AAAs. It might be of great importance to correct preoperative shock and anemia caused by massive bleeding before the onset of hemodynamic deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
3
0
3
Order By: Relevance
“…Although the size of the aneurysm, female sex as well as current smoking, rapid growth, and hypertension have been identified as independent variables, little is known on how external circumstances may trigger AAA rupture. 1,21,[24][25][26][27][28][29] Although several studies aimed to find a relation between weather conditions and the incidence of major cardiovascular emergencies, 9,30,31 there is only little evidence on how far the meteorological parameters may contribute to aortic ruptures. In recently published studies, Verberkmoes et al 30 and Ishikawa et al 9 report that the number of daily admissions due to type A dissections and acute myocardial infarction were triggered by low temperature, whereas admissions due to RAAA were independent from meteorological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the size of the aneurysm, female sex as well as current smoking, rapid growth, and hypertension have been identified as independent variables, little is known on how external circumstances may trigger AAA rupture. 1,21,[24][25][26][27][28][29] Although several studies aimed to find a relation between weather conditions and the incidence of major cardiovascular emergencies, 9,30,31 there is only little evidence on how far the meteorological parameters may contribute to aortic ruptures. In recently published studies, Verberkmoes et al 30 and Ishikawa et al 9 report that the number of daily admissions due to type A dissections and acute myocardial infarction were triggered by low temperature, whereas admissions due to RAAA were independent from meteorological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The current study suggests that total body iron overload is not present in patients with AAA. Furthermore, several studies have identified iron deficiency anaemia as a significant predictor for mortality in AAA patients (12,(29)(30)(31)(32). It is therefore unlikely that iron restriction would be beneficial (and may even be harmful) for AAA patients.…”
Section: Discussionmentioning
confidence: 99%
“…23 Unfortunately, minimally invasive approaches may not be possible in all situations. Intraoperative massive hemorrhage 24 and subsequent hemostasis need better exposure of the surgical field, which means redamage to subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%